Energy intensity improvement potential of the commercial buildings in developing countries: A case study of Nepal - Shakya, Shree Raj; Sah, Janu Kumar; Bhujel, Puja; Aryal, Hricha; Bajracharya, Tri Ratna; Bhandari, Ramchandra; Subedi, Subarna; Chaulagain, Bibish (Journal of Innovations in Engineering Education, 2024)
The need for building-related energy is increasing, mostly in developing countries where urbanization is taking place rapidly with ever-increasing demand in commercial and public services. Globally, energy efficiency is emphasized as a key strategy for addressing rising energy demand and decoupling energy from economic growth. In order to assess the existing status and potential for energy savings in developing nations like Nepal, we compared the energy intensity with and without biomass among Nepal, India, China, and Germany during 2000–2020. This study uses the typical service sector building, as case study, to examine the potential for building energy savings using various passive and active solutions. It explores the various energy efficient measures by simulating the building's energy system with OpenStudio-EnergyPlus. The bioclimatic chart was used to analyze climate factors and passive design strategies. The questionnaire survey was conducted with the occupants of the building. This study has identified energy-saving opportunities and their economic viability. Finally, the energy use intensity (EUI) of the project site was evaluated. The study's findings and methodologies used can be emulated during development of national standards for commercial buildings for Nepal and other countries promoting building energy efficiency.